Comparison of three-dimensional cell culture techniques of dedifferentiated liposarcoma and their integration with future research - Tahara, Sayumi; Sharma, Soumya; de Faria, Fernanda Costas Casal; Sarchet, Patricia; Tomasello, Luisa; Rentsch, Sydney; Karna, Roma; Calore, Federica; Pollock, Raphael E. (Frontiers in Cell and Developmental Biology, 2024)
Background: Dedifferentiated liposarcoma is a formidable sarcoma subtype due to its high local recurrence rate and resistance to medical treatment. While 2D cell cultures are still commonly used, 3D cell culture systems have emerged as a promising alternative, particularly scaffold-based techniques that enable the creation of 3D models with more accurate cell-stroma interactions. Objective: To investigate how 3D structures with or without the scaffold existence would affect liposarcoma cell lines (Lipo246 and Lipo863) growth morphologically and biologically. Methods: Lipo246 and Lipo863 cell lines were cultured in 3D using four different methods; Matrigel ECM scaffold method, Collagen ECM scaffold method, ULA plate method and Hanging drop method, in addition to conventional 2D cell culture methods. All samples were processed for histopathological analysis (HE, IHC and DNAscope), western blot, and qPCR; moreover, 3D collagen-based spheroids were treated with different doses of SAR405838, a well-known inhibitor of MDM2, and cell viability was assessed in comparison to 2D model drug response. Results: Regarding morphology, cell lines behaved differently comparing the scaffold-based and scaffold-free methods. Lipo863 formed spheroids in Matrigel but not in collagen, while Lipo246 did not form spheroids in either collagen or Matrigel. On the other hand, both cell lines formed spheroids using scaffold-free methods. All samples retained liposarcoma characteristic, such as high level of MDM2 protein expression and MDM2 DNA amplification after being cultivated in 3D. 3D collagen samples showed higher cell viability after SAR40538 treatment than 2D models, while cells sensitive to the drug died by apoptosis or necrosis. Conclusions: Our results prompt us to extend our investigation by applying our 3D models to further oncological relevant applications, which may help address unresolved questions about dedifferentiated liposarcoma biology.